Paradigm Shifts in the Interpretation of Heaven Illustration Among Indonesian Mufassir: A Comparative Analysis of As-Singkili, Hamka, and M. Quraish - Saifuddin Herlambang; Wendi Parwanto (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This article examines the changes in the interpretation of the illustration of heaven among Indonesian mufassirin (interpreters), including As-Singkili, Hamka, and M. Quraish Shihab, using Thomas Kuhn's paradigm shift theory. The study reveals a shift in the meaning of the illustration of heaven in each generation of interpreters in Indonesia, particularly in the areas of the width of heaven, the river that flows beneath heaven, fruits in heaven, spouses and houris (heavenly virgins) in heaven, and the color green and adornment for humans in heaven. The article concludes that As-Singkili's interpretation is considered normal science as it remains literal, whereas Hamka and M. Quraish Shihab's interpretations are categorized under scientific revolution due to the rationalization and development of their interpretations still based on normal science or literal texts. This study contributes to a deeper understanding of the evolution of interpretation of Islamic texts in Indonesia.